Kuhn's evolutionary social epistemology - Wray, K. Brad, 1963- (Cambridge University Press, 2011)
"Kuhn's Structure of Scientific Revolutions (1962) has been enduringly influential in philosophy of science, challenging many common presuppositions about the nature of science and the growth of scientific knowledge. However, philosophers have misunderstood Kuhn's view, treating him as a relativist or social constructionist. In this book, Brad Wray argues that Kuhn provides a useful framework for developing an epistemology of science that takes account of the constructive role that social factors play in scientific inquiry. He examines the core concepts of Structure and explains the main characteristics of both Kuhn's evolutionary epistemology and his social epistemology, relating Structure to Kuhn's developed view presented in his later writings. The discussion includes analyses of the Copernican revolution in astronomy and the plate tectonics revolution in geology. The book will be useful for scholars working in science studies, sociologists and historians of science as well as philosophers of science"--